2019
DOI: 10.1101/840033
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epithelial Vegfa specifies a distinct endothelial population in the mouse lung

Abstract: Manuscript 2 SUMMARY:The lung microvasculature is essential for gas exchange and commonly considered homogeneous. We show that Vascular endothelial growth factor A (Vegfa) from the epithelium specifies a distinct endothelial cell (EC) population in the postnatal mouse lung. Vegfa is predominantly expressed by alveolar type 1 (AT1) cells and locally required to specify a subset of ECs. Single cell RNA-seq identified 15-20% lung ECs as transcriptionally distinct and marked by Carbonic anhydrase 4 (Car4), which a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
37
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(45 citation statements)
references
References 55 publications
7
37
1
Order By: Relevance
“…The expression of the proliferation marker was observed in a few iAT1 cells at single-cell resolution ( Figure 7D,E), but, since the FD-AO culture was started only with iAT2 cells, it would be considered that most iAT1 cells differentiated from iAT2 cells. While recent reports indicated that AT1 cells expressed VEGFA and were a heterogeneous population including IGFBP2 + AT1 cells, 22,23 we were not able to identify this subpopulation of iAT1 cells, suggesting that XAV-939 would homogeneously induce iAT1 cells ( Figure 7E). Although in vitro regeneration models 5,15,24 and an iPSC differentiation model 24 cells that were not treated with XAV-939 treatment ( Figure 5E), suggesting that there is another endogenous mechanism through which Wnt signaling is inhibited and iAT2-to-iAT1 differentiation is promoted.…”
Section: Discussioncontrasting
confidence: 77%
“…The expression of the proliferation marker was observed in a few iAT1 cells at single-cell resolution ( Figure 7D,E), but, since the FD-AO culture was started only with iAT2 cells, it would be considered that most iAT1 cells differentiated from iAT2 cells. While recent reports indicated that AT1 cells expressed VEGFA and were a heterogeneous population including IGFBP2 + AT1 cells, 22,23 we were not able to identify this subpopulation of iAT1 cells, suggesting that XAV-939 would homogeneously induce iAT1 cells ( Figure 7E). Although in vitro regeneration models 5,15,24 and an iPSC differentiation model 24 cells that were not treated with XAV-939 treatment ( Figure 5E), suggesting that there is another endogenous mechanism through which Wnt signaling is inhibited and iAT2-to-iAT1 differentiation is promoted.…”
Section: Discussioncontrasting
confidence: 77%
“…4E, F and Table S2). These changes were confirmed in a metagene analysis using AT1 and AT2 gene signatures derived from scRNA-seq of E19 lungs (26), as well as our published 119 progenitor genes (11) ( Fig. 4G, Table S3, Table S4).…”
Section: Single-cell Rna-seq Profiling Of Post-lung-specification Lefsupporting
confidence: 78%
“…Raw data have been deposited in GEO under the accession number GSE144170. AT1 and AT2 gene lists are from the following dataset: GSE124325 (26).…”
Section: Cell Dissociation and Facs For Scrna-seqmentioning
confidence: 99%
“…In the absence of Car4 ECs, despite the normal appearance of myofibroblasts, alveolar space is aberrantly enlarged. These observations indicate a signaling role of AT1 cells [ 79 ]. Importantly, overexpression of VEGF in newborn mice induces inducible nitric oxide synthase (iNOS) and eNOS-dependent lung simplification, pulmonary edema, and oxidant stress.…”
Section: Deregulated Signaling Pathwaysmentioning
confidence: 99%